The NaV1.7 Channel Subtype as an Antinociceptive Target for Spider Toxins in Adult Dorsal Root Ganglia Neurons - Gonçalves, Tânia C.; Benoit, Evelyne; Partiseti, Michel; Servent, Denis (Frontiers in Pharmacology, 2018)
Although necessary for human survival, pain may sometimes become pathologic if long-lasting and associated with alterations in its signaling pathway. Opioid painkillers are officially used to treat moderate to severe, and even mild, pain. However, the consequent strong and not so rare complications that occur, including addiction and overdose, combined with pain management costs, remain an important societal and economic concern. In this context, animal venom toxins represent an original source of antinociceptive peptides that mainly target ion channels (such as ASICs as well as TRP, CaV, KV and NaV channels) involved in pain transmission. The present review aims to highlight the NaV1.7 channel subtype as an antinociceptive target for spider toxins in adult dorsal root ganglia neurons. It will detail (i) the characteristics of these primary sensory neurons, the first ones in contact with pain stimulus and conveying the nociceptive message, (ii) the electrophysiological properties of the different NaV channel subtypes expressed in these neurons, with a particular attention on the NaV1.7 subtype, an antinociceptive target of choice that has been validated by human genetic evidence, and (iii) the features of spider venom toxins, shaped of inhibitory cysteine knot motif, that present high affinity for the NaV1.7 subtype associated with evidenced analgesic efficacy in animal models.